Instantaneous ambiguity resolution in global-navigation-satellite-system-based determination applications: A multivariate constrained approach - Giorgi, G.; Teunissen, Peter; Verhagen, S.; Buist, P. (American Institute of Aeronautics and Astronautics, Inc., 2012)
Carrier phase integer ambiguity resolution is the key to high-precision Global Navigation Satellite System (GNSS) positioning, navigation, and attitude determination. It is the process of resolving the unknown cycle ambiguities of the carrier phase data as integers. After ambiguity resolution, precise baseline estimates become available, which can be used to derive the attitude of a multi-antenna platform. The purpose of this contribution is to present and test a rigorous GNSS-based attitude determination method, optimally exploiting the complete set of geometrical constraints. The key to this new method is an extension of the popular LAMBDA method: the multivariate constrained LAMBDA. The method estimates the integer ambiguities and the platform’s attitude in an integralmanner, fully exploiting the known body geometry of the multi-antenna configuration. As a result, the ambiguity resolution performance is greatly improved. The method is extensively tested addressing the most challenging scenario: single-epoch single-frequency GNSS observations are processed without any filtering, external aid, or dynamic modeling.